Detección y genotipificación de rotavirus en pacientes con gastroenteritis aguda - Weilg Espejo, Pablo (2014)
Background: Gastroenteritis by rotavirus is responsible for approximately 810 annual deaths/year in children under 5 years in Peru and emerging rotavirus genotypes have led to concerns regarding cross-protection by the vaccines available. Moreover, there are no reports on the molecular-epidemiology of rotavirus diarrhea in Peru Methodology: A total of 131 stool samples were obtained from children under 5 years old hospitalized from January 2010 to December 2012 in the Hospital Regional de Cajamarca, Peru. ELISA and RT-PCR techniques were performed for rotavirus detection. G and P typing of rotavirus-positive samples were obtained by semi-nested multiplex RT-PCR and sequencing was performed to confirm the PCR results. Results: Of the 117 samples available, 18.80% (22/117) tested positive for rotavirus by ELISA and 35.90% (42/117) by RT-PCR. Among the G-genotype identified, G9 in 35.71% (15/42) and G12 in 33.33% (14/42) were the most prevalent. With the most common combination being G12/P6 in 23.81% (10/42). Conclusions: A high prevalence of the G12/P6 genotype was detected. It is know that this genotype is not covered by the current vaccines available. More in depth studies are needed to know the current rotavirus genotypes presents in Peru.